2010
DOI: 10.1098/rspb.2009.2163
|View full text |Cite
|
Sign up to set email alerts
|

Unparalleled rates of species diversification in Europe

Abstract: The most rapid species radiations have been reported from 'evolutionary laboratories', such as the Andes and the Cape of South Africa, leading to the prevailing view that diversification elsewhere has not been as dramatic. However, few studies have explicitly assessed rates of diversification in northern regions such as Europe. Here, we show that carnations (Dianthus, Caryophyllaceae), a well-known group of plants from temperate Eurasia, have diversified at the most rapid rate ever reported in plants or terres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
233
7
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(273 citation statements)
references
References 54 publications
22
233
7
2
Order By: Relevance
“…The rate of freshwater Gammarus is comparable with fastest-diversifying bivalves 0.09 sp/My (17) and ground beetles 0.10 sp/My (18). However, it is slower than that of Mediterranean plants, such as Dianthus carnations, which have a rate of 2.2-7.6 sp/My (19), and Brassicaceae mustard 0.18-0.22 sp/My (20). The ancient Tethyan region is one of the hotspots of global biodiversity for both terrestrial and aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 90%
“…The rate of freshwater Gammarus is comparable with fastest-diversifying bivalves 0.09 sp/My (17) and ground beetles 0.10 sp/My (18). However, it is slower than that of Mediterranean plants, such as Dianthus carnations, which have a rate of 2.2-7.6 sp/My (19), and Brassicaceae mustard 0.18-0.22 sp/My (20). The ancient Tethyan region is one of the hotspots of global biodiversity for both terrestrial and aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, we have found that most hybridizing species are non-relict, and are interbreeding with phylogenetically related species ( Table 2). As a consequence of the rapid diversification rate undergone by many Mediterranean plant lineages, many allopatric endemic species with weak reproductive isolation exist (Valente et al 2010;Gutiérrez-Larena et al 2002). Under these circumstances, we presume that the observed hybridization will lead to introgression.…”
Section: An Example: Climate Change and Hybridization In The Sierra Nmentioning
confidence: 98%
“…One main feature of the Mediterranean flora is its high rate of diversification, with most of the current diversity in this region having evolved very recently as the consequence of the segregation of widespread taxa into populations isolated on the many mountaintops that form the complex Mediterranean landscape (Valente et al 2010). Most Mediterranean high-mountain plants therefore belong to young lineages with related species inhabiting the surrounding lowlands, a feature that may enhance the probability of hybridization after secondary contact.…”
Section: An Example: Climate Change and Hybridization In The Sierra Nmentioning
confidence: 99%
“…2, Test 1; Appendix S4) represent three major phylogenetic clades (rosids, caryophyllids, and asterids) that have undergone recent, explosive radiations (e.g., Liu et al, 2006;Valente et al, 2010;Zhang et al, 2017b). These groups were the main consideration during design of the standard primer sets because they represent so much plant diversity at the species level.…”
Section: Discussionmentioning
confidence: 99%